2022
DOI: 10.1093/jtm/taac044
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of severe altitude illness symptoms in Mt. Kilimanjaro hikers: a prospective cohort study

Abstract: Background: Each year several Mt. Kilimanjaro hikers die due to altitude illness although urgent descent is technically easily possible. The objectives of this study were to determine the incidence and predictors of severe altitude illness symptoms and of summit success in Mt. Kilimanjaro hikers, and the measures taken when altitude illness symptoms develop. Methods: A prospective observational cohort study in Mt. Kilimanjaro hikers was conducted from December 2019 until March 2020. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…High-altitude regions have low oxygen, extreme cold temperatures, and high radiation levels, all of which having a profound impact on the structure and function of the intestinal flora. The Qinghai–Tibet Plateau in China is the largest plateau area in the world, and visitors experience symptoms of discomfort, especially headache, chest tightness, nausea, and vomiting ( Wen et al, 2014 ; Croughs et al, 2022 ). Kleessen et al (2005) reported that dysbiosis, in which pathogenic bacteria increase and probiotics decrease, often occurs in plateau populations.…”
Section: Introductionmentioning
confidence: 99%
“…High-altitude regions have low oxygen, extreme cold temperatures, and high radiation levels, all of which having a profound impact on the structure and function of the intestinal flora. The Qinghai–Tibet Plateau in China is the largest plateau area in the world, and visitors experience symptoms of discomfort, especially headache, chest tightness, nausea, and vomiting ( Wen et al, 2014 ; Croughs et al, 2022 ). Kleessen et al (2005) reported that dysbiosis, in which pathogenic bacteria increase and probiotics decrease, often occurs in plateau populations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, allowing ample time for recovery and acclimatization is pivotal for safety at high altitudes (34,39,41). The primary treatment for severe altitude sickness revolves around rapid descent from high altitudes, coupled with oxygen therapy.…”
Section: Symptoms and Managementmentioning
confidence: 99%
“…The primary treatment for severe altitude sickness revolves around rapid descent from high altitudes, coupled with oxygen therapy. Additionally, medications like acetazolamide, dexamethasone, and nifedipine might be considered as part of the treatment protocol (34).…”
Section: Symptoms and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have shown that poor knowledge is accompanied by an increased risk of altitude illness, while greater knowledge is associated with a lower incidence of altitude illness. (Croughs et al , 2022;Gaillard et al , 2004;Hackett et al , 1976;Kayser, 1991;McDevitt et al , 2014;Shlim and Gallie J, 1992) Although a lack of knowledge may affect the risk of developing acute altitude illness, no resources have defined the appropriate baseline level of knowledge about high-altitude physiology and medicine for laypersons traveling to high altitude. The overwhelming majority of consensus statements and guidelines are intended for healthcare professionals, trekking or expedition leaders, or mountain guides (Kupper, 2020;Kupper et al , 2012) and do not specifically target laypersons.…”
Section: Introductionmentioning
confidence: 99%